Circulating tumor cells as a longitudinal biomarker in patients with advanced chemorefractory, RAS‐BRAF wild‐type colorectal cancer receiving cetuximab or panitumumab. Issue 6 (4th March 2015) - Musella, Valeria; Pietrantonio, Filippo; Di Buduo, Eleonora; Iacovelli, Roberto; Martinetti, Antonia; Sottotetti, Elisa; Bossi, Ilaria; Maggi, Claudia; Di Bartolomeo, Maria; de Braud, Filippo; Daidone, Maria Grazia; Cappelletti, Vera
<x xml:space="preserve">Abstract</x> A still relevant number of patients with RAS‐BRAF wild‐type colorectal cancer (CRC) do not respond to treatment with antiepidermal growth factor receptor (EGFR) monoclonal antibodies cetuximab and panitumumab, suggesting that additional biomarkers to guide patient selection are urgently needed. Circulating tumor cells (CTCs) may represent such a biomarker. In this prospective study, 38 patients with advanced RAS‐BRAF‐wild‐type CRC received third‐line therapy with cetuximab‐irinotecan or panitumumab. Peripheral blood samples for CTC status determination were collected at baseline, during treatment at early (2–4 weeks) and at later (8–10 weeks) times. CTC enrichment was done with the AdnaTest ColonCancerSelect kit, whereas CTC detection was done with the AdnaTest ColonCancerDetect kit. CTC status positivity was defined according to the kit manufacturer's thresholds. Fifty percent of patients were defined as CTC positive at baseline and the overall RECIST response rate was 26%. CTC baseline status was not associated with treatment response, whereas early CTC status and CTC status changes during treatment were significantly associated with tumor response. Kaplan‐Meier analysis showed a significantly shorter progression‐free survival (median, 2.0 versus 4.0 months, p = 0.004) and overall survival (4.7 versus11.4, p = 0.039) in patients with early CTC + status compared with CTC ‐ ones. In multivariable analysis including classical prognostic factors, the CTC status changes profile during treatment was an independent predictor of both progression‐free survival (p < 0.001) and overall‐survival (p = 0.001). CTC status assessed early during treatment with anti‐EGFR monoclonal antibodies may predict treatment failure in advance compared to imaging‐based tools.